Comparison of regression for blood ALP levels using methods of the Japan Society of Clinical Chemistry and the International Federation of Clinical Chemistry and Laboratory Medicine in bovine, canine, feline, and human testing. - Akihisa Hata (Public Library of Science (PLoS), 2021)
Livestock and companion animal health have a direct impact on human health. Research on clinical laboratory technology for veterinary medicine is as important as that on human laboratory technology. Reagents and analysis equipment for human medical laboratory tests are often used in veterinary medicine. Medical laboratories in Japan utilize the Japan Society of Clinical Chemistry (JSCC) method for blood alkaline phosphatase (ALP) analysis. The International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) method is used worldwide for ALP catalytic concentration measurement. When the IFCC method is used, human blood ALP activity is approximately one-third of the JSCC method's activity. The JSCC method for ALP measurement was switched to the IFCC method in medical laboratories in Japan in April 2020 for global standardization purpose. It is uncertain whether conventional JSCC method reagents will continue to be supplied. In veterinary medicine, the relationship between the JSCC and IFCC methods in terms of ALP measurement is almost unclear. This study investigated the regression between JSCC and IFCC methods measuring ALP in bovine, canine, feline, and human. The regression formulas for bovine, canine, feline, and human ALP values using the conventional JSCC (x) and IFCC (y) methods are y = 0.379x + 0.124, y = 0.289x + 8.291, y = 0.358x + 0.432, and y = 0.337x + 2.959, respectively. These results suggested that the IFCC method measurement could be estimated by approximately one-third of the JSCC method measurement in animal species such as bovine, canine, and feline. By applying the conversion factors proposed in this study, a very good correlation could be obtained between the two methods for each animal.